2011
DOI: 10.1135/cccc2011053
|View full text |Cite
|
Sign up to set email alerts
|

Do the mercaptocarbene (H–C–S–H) and selenocarbene (H–C–Se–H) congeners of hydroxycarbene (H–C–O–H) undergo 1,2-H-tunneling?

Abstract: Dedicated to our colleague Zdeněk Havlas for his contributions to computational chemistry and on the occasion of his 60th birthday.The principal purpose of this investigation is the determination of the tunneling half-lives of the trans-HCSH → H 2 CS and the trans-HCSeH → H 2 CSe unimolecular isomerization reactions at temperatures close to 0 K. To aid these determinations, accurate electronic structure computations were performed, with electron correlation treatments as extensive as CCSDT(Q) and basis sets as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 79 publications
1
17
0
1
Order By: Relevance
“…This short path explains why a sizeable barrier of 34.29 kcal mol À1 can be passed very efficiently by tunneling. Long lifetimes were found for the higher hydroxycarbene congeners H-C-S-H and H-C-Se-H. [55] To further elucidate the effect of the mass of the contributing particles and their chemical influence on the barrier, several substituted carbenes were investigated. These carbenes have not, to the authors knowledge, been measured in the lab yet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This short path explains why a sizeable barrier of 34.29 kcal mol À1 can be passed very efficiently by tunneling. Long lifetimes were found for the higher hydroxycarbene congeners H-C-S-H and H-C-Se-H. [55] To further elucidate the effect of the mass of the contributing particles and their chemical influence on the barrier, several substituted carbenes were investigated. These carbenes have not, to the authors knowledge, been measured in the lab yet.…”
Section: Resultsmentioning
confidence: 99%
“…This short path explains why a sizeable barrier of 34.29 kcal mol −1 can be passed very efficiently by tunneling. Long lifetimes were found for the higher hydroxycarbene congeners H‐C‐S‐H and H‐C‐Se‐H 55…”
Section: Resultsmentioning
confidence: 99%
“…With thioformaldehyde (H 2 CS; p1) residing ubiquitously in star-forming regions and branching ratios of thioformaldehyde to thiohydroxycarbene of typically three to one derived from the present study, fractional abundances of thiohydroxycarbene of up to 10 −9 with respect to molecular hydrogen are predicted. Consequently, the prospective detection of trans/cis thiohydroxycarbene, which have dipole moments of 1.8 and 2.6 Debye, respectively (33), would be invaluable to test future chemical models of the organosulfur chemistry in star-forming regions. In terrestrial laboratories, all previous attempts to detect trans/cis-thiohydroxycarbene spectroscopically in the gas phase or in low-temperature matrices were unsuccessful, although Lamberts suggested that thiohydroxycarbene should represent a reactive intermediate in the hydrogenation of carbonyl monosulfide (CS) on interstellar grains (44).…”
Section: Discussionmentioning
confidence: 99%
“…In terrestrial laboratories, all previous attempts to detect trans/cis-thiohydroxycarbene spectroscopically in the gas phase or in low-temperature matrices were unsuccessful, although Lamberts suggested that thiohydroxycarbene should represent a reactive intermediate in the hydrogenation of carbonyl monosulfide (CS) on interstellar grains (44). The high reactivity, even in lowtemperature matrices, might be associated with the molecular structure of thiohydroxycarbene, suggesting that thiohydroxycarbene is not a true carbene, but, rather, a ylide with a negatively charged carbon atom and a positively charged sulfur atom (33). However, the vast regions of space represent a unique natural laboratory on a macroscopic scale and, hence, an unprecedented opportunity to search for highly reactive molecules such as thiohydroxycarbene.…”
Section: Discussionmentioning
confidence: 99%
“…Proton tunneling is estimated by way of the WKB approximation. The WKB tunneling calculation has been used in describing tunneling in chemical reactions involving enolization of 2‐methylacetophenone, H shift in silacetylene and Phenylhydroxycarbene, γ H abstraction in ketones, rearrangement reactions of cyclopropylcarbenes, proton “ring walks” in benzenium ions, mercapto and selocarbenes, and NH 2 radical reactions with methane.…”
Section: Methodsmentioning
confidence: 99%